Liberating Supply-Fiscal Policy and Technological innovation in a Multicountry Model - Laxton, Douglas (IMF Working Papers; Working Paper ;, 1998)
This paper examines how endogenizing technological progress in a multicountry macroeconometric model affects the analysis of fiscal policies. It uses an expanded version of the IMF's multicountry model, MULTIMOD, in which total factor productivity (TFP) is endogenized as a function of domestic research and development (R and D) expenditures, R and D expenditures of trading partners, and trade. Compared with the standard version of the model with exogenous TFP, fiscal policies have much larger and long-lived effects on the domestic economy and on other countries.